The impact of digital training and mentoring on early childhood education teachers’ knowledge and practices related to nutrition and health - Herawati Netti; B Nuraeni; R Efendi; Y Herlina; N Kusumaningtyas; Zam R Zam; Rudianto; Y Natakusuma; AM Ramadhan (BIO Web of Conferences)
This pre-post intervention study aims to evaluate the impact of digital training and mentoring on early childhood education (ECE) teachers' knowledge and practices related to nutrition and health. The sample consisted of 963 teachers with a minimum of two years of experience. Teachers participated in two days of digital training program, while mentors underwent three days of training and received monthly technical guidance through digital sessions. They mentored teachers before the implementation phase and conducted monitoring sessions twice a month during four months of implementation. A paired-sample t-test revealed a significant increase in teachers' scores, from 61 to 71 (p = 0.019), exceeding the minimum standard (score ≥70). The proportion of ECE teachers with scores according to minimum standards (≥70) before intervention was 39% and significantly increased to 57%. The digital training with mentoring significantly increased the ECE teachers’ knowledge and practices of nutrition and health. All competency items also significantly increased. All teachers implemented the nutrition programs, provided health services, and created a healthy school environment in ECE centers. They submit anthropometric data and tuberculosis incidence reports every month. We recommend the future research design training material based on the teacher assessment, focusing on topics that teachers have not yet mastered. Additionally, research questions should be designed to explore the underlying reasons for observed outcomes.